The Role of Osteopontin and Visfatin as Diagnostic Markers in Thyroid Disorders - Shammar, Samar Hasan (Medical Science Journal for Advance Research, 2025)
Background: Both Osteopontin and Visfatin remain underexplored in the context of thyroid disorders. Nonetheless, taking into account their association with inflammation and metabolic alterations, further investigation on OPN and Visfatin is necessary within the scope of thyroid disorders. Initial biomarker stage for disease progress can enhance diagnosis, monitoring, and checkup frequency. Biochemical changes in the endocrine system signal the presence of disturbances in the body systems. Evaluation of thyroid diseases and the biology of ossification is essential because they are prevalent pathologies in the population. Osteopontin plays an essential role in the development, growth and metabolic activities of cells resulting in bone tissue architecture. Functions of Visfatin in governing metabolic processes appear relatively novel. Objectives: This first study, we hope to make an attempt in examining the diagnostic value of serum OPN and Visfatin levels among thyroid disease patients. Moreover, identify differences between thyroid disease patients and matched healthy participants concerning serum levels of Osteopontin and Visfatin. Methods: The study conducted is a case-control study of 60 patients with thyroid disease and 60 healthy controls. Blood samples were collected, from which serum Osteopontin and Visfatin levels were quantified. Correlation between Visfatin, Osteopontin, age, and BMI, and other background variables were also conducted. Results: Osteopontin and Visfatin levels in patients with Thyroid disease and controls will be discussed. In patients with thyroid disease, Osteopontin levels were significantly lower (4.13 ± 1.40 μg/L) than in controls (6.20 ± 1.91 μg/L) (p = 0.001). Visfatin levels were significantly greater in the patients (3.49 ± 0.53 ng/mL) than in controls (1.8 ± 0.18 ng/mL) (p = 0.01). No significant correlation was observed between Osteopontin and age/BMI (p > 0.05). There was a weak correlation noted between Visfatin and BMI (p = 0.037). Conclusion: These results imply that Osteopontin and Visfatin might be considered potential markers for thyroid disease. The outlined results suggest biphasic changes in OPN and Visfatin as a part of a particular biochemical pattern associated with thyroid dysfunction, lower OPN and higher Visfatin possibly indicating inflammatory and metabolic derangement in thyroid disease.